Global Trends in Spiritual and Palliative Intervention in Cancer Patients: Bibliometric Analysis - Sukwan Sumono; Erna Rochmawati (Indonesian Journal of Global Health Research, 2026)
Advanced cancer patients often experience multidimensional suffering known as "Total Pain," which includes physical, psychological, social, and spiritual distress. While spiritual interventions are recognized as core components of holistic palliative care, a comprehensive global mapping of research trends over the last five decades remains limited. This study aims to explore global publication trends, identify influential countries and authors, and map key thematic clusters in spiritual intervention research for cancer patients from 1973 to 2025. A quantitative bibliometric design was used. Bibliographic data of 1,121 documents were extracted from the Scopus database following PRISMA 2020 protocols. Data analysis evaluated publication performance and geographic distribution. VOSviewer software was used for keyword co-occurrence and network visualization. Publication growth showed three phases: initiation, acceleration, and maturity (post-2011). The United States dominates global publications (42.5%), followed by Canada (7.4%) and the UK (6.4%). A significant rise in research from Iran and China indicates a shift toward de-westernization in spiritual care. The most influential study by Zimmermann et al. (2014) emphasized early palliative care. Four main thematic clusters were identified: spiritual well-being, quality of life, structured interventions (eg, Dignity Therapy), and death anxiety mitigation. Spiritual intervention research has evolved into a high-level health science. Integrating structured spiritual protocols into early palliative care is essential to address existential distress in terminal cancer patients.